EFEKTIFITAS METODE PRA (PARTICIPATION RURAL APPRAISAL) DALAM PENGENTASAN KELUARGA MISKIN DI PROPINSI LAMPUNG - Elly Kumari Tjahja Putri (Sosio Informa, 2003)
The monetary crisis that began in 1998, followed by multidimensional one, had induced a widespread impacts on many aspects of the national political, economical, social and culturallives. This condition is strongly related to the unsound strategy of development implemented by the previous geverment with its centralized, beurocratic and unifornity approach which in turn had the effect of social structure and organization deempowerment of the society. This can be cured by revitalizing self-determination dan social participation of the community to help themselves solving their own problems without government interference. PRA (Participation Rural Appraisal) method could be considered applied to raise etno development with its bottom-up approach in community development. This research is conducted to asses the effectiveness of PRA in empowering the poor in province Lampung. A quasi-experimental method is adopted with single before-after design. Research results revealed that PRA method is not effective enough to increase social participation of the people in Lampung due to unnecessary intervention from the local authority so as to make them unable in making their own decision. In addition, social workers in the location were not functioning well due to lack of capability in applying PRA method, and there were weak partnerships between NGO and local enterpreneur, along with community, to overcome poverty problems. In the future, training on PRA method should be held for local social worker. In addition, there should be effort to grow local social-structure initiatives and creativities without the inference from local government.Key words: PRA (Participation Rural Appraisal), poor empowerment, effectiveness.